Expository text comprehension in secondary school: for which readers does knowledge of connectives contribute the most?. (17th November 2016) - Welie, Camille; Schoonen, Rob; Kuiken, Folkert; van den Bergh, Huub
Abstract : The present study examined whether knowledge of connectives contributes uniquely to expository text comprehension above and beyond reading fluency, general vocabulary knowledge and metacognitive knowledge. Furthermore, it was examined whether this contribution differs for readers with different language backgrounds or readers who vary in reading fluency, general vocabulary knowledge or metacognitive knowledge levels. Multilevel regression analyses revealed that knowledge of connectives explained individual differences in eighth graders' text comprehension ( n = 171) on top of the variance accounted for by the control variables. Moreover, the contribution of knowledge of connectives to text comprehension depended on a reader's level of metacognitive knowledge: more metacognitive knowledge resulted in a larger association between knowledge of connectives and text comprehension. Reading fluency, vocabulary knowledge and language background did not interact with knowledge of connectives. Findings are interpreted in the context of the strategic use of connectives during expository text reading. What is already known about this topic? Connectives (words such as moreover, because and although) help the reader in establishing coherence between text parts. In primary school, for fifth graders, knowledge of connectives has been shown to be uniquely related to English text comprehension controlling for reading fluency and general vocabulary knowledge. For fifth graders, the relationship between knowledge of connectives and English text comprehension was higher for English‐only students than for their peers who learned English as a second language. What this paper adds: The present study found that knowledge of connectives also has a unique relation with Dutch expository text comprehension for eighth graders above and beyond reading fluency, general vocabulary knowledge and metacognitive knowledge (about text structure and reading and writing strategies). The relationship between knowledge of connectives and text comprehension was not moderated by reading fluency, general vocabulary knowledge and language background (monolingual versus bilingual Dutch). Metacognitive knowledge did impact the relationship between knowledge of connectives and text comprehension: the higher the metacognitive knowledge, the higher the association between knowledge of connectives and text comprehension. Implications for theory, policy or practice Secondary school readers are assumed to benefit from knowing connectives because these words are frequent in expository texts and signal relationships that students may often not infer without the help of these devices (i.e., with the use of background knowledge). This seems to apply in particular for expository texts that are intended to convey new information and relationships to students (see also Singer & O'Connell, 2003 ). We found a significant interaction between knowledge of connectives and metacognitive knowledge, which seems to indicate that knowing more connectives does not help much in improving expository text comprehension when metacognitive knowledge about text structure and reading strategies is low. This result suggests that it may be wise to couple instruction on the meaning of connectives with instruction about the structure of expository texts and ways to strategically deal with these texts. More specifically, besides instruction on the meaning of connectives, we advise teachers in secondary school to get students to understand the importance of connectives as markers of local and global coherence in texts, and to teach them how to strategically use connectives during reading.